MECHANICAL FUSE DEVICE FOR PROTECTING SWITCHING APPARATUS - CHAUHAN, Shashwat (2024)
Embodiments herein provide a mechanical fuse device (50) for a drive shaft (82) of a switching apparatus (200). The fuse device (50) comprising a first connection portion (42) and a second connection portion (44), and a neck portion (46) connecting the first connection portion (42) and the second connection portion (44). The drive shaft (82) comprises a first part (82a) and a second part (82b). The first connection portion (42) is configured to be removably connected to the first part (82a) and the second connection portion (44) is configured to be removably connected to the second part (82b) thereby connecting the first part (82a) and the second part (82b) of the drive shaft (82). The neck portion (46) is a weak link configured to break when being subject to a torque exceeding a predetermined torque value and thereby disconnect the first part (82a) and the second part (82b) of the drive shaft (82). Des modes de réalisation de la présente invention concernent un dispositif de fusible mécanique (50) pour un arbre primaire (82) d'un appareil de commutation (200). Le dispositif de fusible (50) comprend une première partie de connexion (42) et une seconde partie de connexion (44), ainsi qu'une partie de col (46) qui relie la première partie de connexion (42) et la seconde partie de connexion (44). L'arbre primaire (82) comprend une première partie (82a) et une seconde partie (82b). La première partie de connexion (42) est configurée pour être connectée de manière amovible à la première partie (82a) et la seconde partie de connexion (44) est configurée pour être connectée de manière amovible à la seconde partie (82b), reliant ainsi la première partie (82a) et la seconde partie (82b) de l'arbre primaire (82). La partie col (46) est un maillon faible conçu pour se rompre lorsqu'il est soumis à un couple dépassant une valeur de couple prédéterminée et désolidariser ainsi la première partie (82a) et la seconde partie (82b) de l'arbre primaire (82).